Impelementation of Scientific Based Prezi Presentation Media to Improve Creative Thinking Skills of Class 8th Students of SMPN 6 Makassar - Saputra, Rezwandy Wahyudi; Tawil, Muh.; Arsyad, Arie Arma (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2023)
This study aims to determine (1) the magnitude of the increase in students' creative thinking skills after applying scientific-based Prezi presentation media. (2) large Effect Size of the application of scientific-based Prezi presentation media to improve students' creative thinking skills (3) a significant increase in the average score of students' creative thinking skills after applying scientific-based Prezi presentation media (4) there is no difference in the average score of creative thinking skills of grade VIII G and class VIII H students after applying scientific-based Prezi presentation media. The population was all class VIII SMPN 6 Makassar consisting of 11 classes with a total of 381 people.The sample in the study VIII G consisted of 35 students and VIII H consisting of 31 students with a total sample of 66 students. The test used is an essay test obtained from pretest and posttest data analyzed using descriptive and inferential statistic.The results of this study were: (1) Improvement of creative thinking skills of students in class VIII Hi SMPN 6 Makassar who were taught using Scientifically based Prezi presentation media obtained N-Gain, which is 0.46 in the medium category. (2) the level of results of the Effect Size analysis of students after the application of Scientifically-based Prezi presentation media in the learning process is 4.48 for class VIII G and 4.68 for class VIII H which is in the Strong Effect category. (3) there was a significant increase in the average score after the application of scientific-based Prezi presentation media. (4) There is no difference in the average N-Gain score of creative thinking skills between class VIII G and class VIII H because both classes are given the same treatment, which is taught using scientific-based Prezi presentation media. This shows that the application of Prezi presentation media can improve students' creative thinking skills.